Deacetylase inhibitors: an advance in myeloma therapy?. Issue 3 (4th March 2017) - Laubach, Jacob P.; San-Miguel, Jesus F.; Hungria, Vania; Hou, Jian; Moreau, Philippe; Lonial, Sagar; Lee, Jae Hoon; Einsele, Hermann; Alsina, Melissa; Richardson, Paul G.
ABSTRACT: Introduction : A significant unmet need exists in patients with relapsed or refractory multiple myeloma (MM), which remains an incurable disease despite recent advances in the field. One such development was the use of deacetylase inhibitors (DACi), which exert unique antimyeloma effects through targeting of epigenetic and protein metabolism pathways. The pan-DACi panobinostat was recently approved in combination with bortezomib and dexamethasone for use in patients with relapsed or relapsed and refractory MM. Results of a phase 3 trial showed that the panobinostat-containing regimen improved the overall response rate and progression-free survival. Panobinostat-associated adverse events included thrombocytopenia, diarrhea, fatigue, and peripheral neuropathy. Research into how to maintain the benefits of DACi while improving tolerability is ongoing. Areas covered : This review focuses on the efficacy and safety of panobinostat and panobinostat-based combinations for MM. Early data from clinical trials investigating the HDAC6 inhibitor ricolinostat are also discussed. Expert commentary : DACi are a unique and effective new class of agents for the treatment of MM, with panobinostat being the first to have clinically meaningful benefit for patients with relapsed or refractory MM. Optimization of dose and schedule, novel combination strategies, and introduction of selective DACi may improve the risk-benefit profile of DACi-based regimens.